Review of the Situation of Human African Trypanosomiasis in the Republic of Congo From the 1950s to 2020 - (:unkn) unknown (My University, 2022)
Abstract Human African trypanosomiasis (HAT), despite considerable progress in the control, is still occurring in many countries in both west and central African regions. The HAT situation in the Republic of Congo has always been overshadowed by its neighbor the Democratic Republic of Congo where over 60% of all HAT cases occur. In the Republic of Congo, HAT cases have been significantly reduced to about 20 reported cases yearly and the disease is still prevalent in few foci across the country. Although continuous assessment of HAT situation in Congo is been led by the National Control Program for HAT, research on the vector, parasite, and vector control has received little attention. Because there have not been enough reviews summarizing key findings from studies conducted so far, there is still a poor understanding of the global situation of HAT in Congo. In order to achieve sustainable elimination of HAT in Congo a deep appraisal of HAT situation is required. The present study provides a review of studies conducted on HAT in the republic of Congo since the 1950s to date in order to identify gaps in knowledge and help consolidate the gains and progress towards the elimination of sleeping sickness.
Keywords: African Research